A Fuzzy Knowledge-Based Approach for End-2-End Behavioural Analysis of Wormhole Attacks on Mobile Ad-Hoc Networks - Imeh Umoren; Ekemini Okpongkpong; Ifreke Udoeka (International Journal of Information Systems and Informatics, 2021)
Mobile Ad hoc Networks (MANETs) involves series of travelling nodes communicating with each other without a fixed Set-up. Certainly, MANETs are networks that utilize communication peripatetic nodes such as; Personal Digital Assistants (PDAs), mobile phones, laptops which enable wireless transmission across an area and forwarding data packets to the other nodes resulting in frequent change in topology. MANETs are exposed to several communication assaults such as active attack and passive attack. The active attack disrupts network operations while the passive attack obtains information without upsetting normal networks operation. Wormhole is a typical case of active attack. Indeed, an attacker receives packets at one end of the network, tunnels them to another end of the network, and then replays them into the networks from that point resulting in a collapse in communication across wireless setups. This research work simulates and models a typical wormhole attack in MANET using Network Simulator (NS-2.35) and Fuzzy Inference System (FIS). The End-2-End behavioural analysis of wormhole attacks on the transmitting networks layer of MANET was realized. To detect the level of wormhole attack in the network several parameters such as Packet Delivery Ratio, Packet Forwarding Probability and Packet Dropping Probability were considered by determining the degree of severity of wormhole attack which may upset the Quality of Service (QOS) delivery. The aim of this research paper is in the direction of Network security optimization.